The Beginning of the End: the Prologue and Epilogues of Hungry Hill and The Glass-Blowers - Eva Leung (Maison de la Recherche en Sciences Humaines, 2021)
This article provides a close reading of the prologue and epilogues of two fictionalised family biographies: Hungry Hill (1943) and The Glass-Blowers (1963). It is not standard practice for Du Maurier to offer prologues and epilogues to her novels, but she ends Hungry Hill with a lengthy epilogue and provides The Glass-Blowers with both a prologue and an epilogue. This article examines the plausible rationales for this aesthetic feature, in terms of the function of contextualisation and characterisation, and analyses how closure is achieved both for the characters concerned and the readers. It shows that the development of these features is not the result of accident, but of narrative experimentation.